Didactics in engineering, basic and advances sciences (ICBA) for mass removal processes: the role of Geography - Teófilo-Salvador, Eduardo (2020)
Humans have always used two main materials: soil and water. However, these materials can produce active and passive processes. The objective was to delimit the technical and methodological scopes for the study of mass removal processes in engineering education, basic and advanced sciences, and interdisciplinary relations with geography. A historical review of geological processes was performed. Methods and techniques were characterized, soil sampling types were applied, and modeling and interpretation with maps were evaluated for model efficiency. Geography, engineering, and earth sciences play a primary role in the study of these phenomena, but the economy is also affected and is reflected in society. It is difficult to control the dynamics of the climate in the generation of surface geological processes, but it is critical to understand several methodologies that allow conceptualizing the process of mass removal to generate more than one solution to a particular problem.